Productive Economic Improvement in the time of COVID-19 Pandemic for the People of Kampung KB Gandul with Innovation of "Mi Jaren" (Palm Sugar Ginger Lemongrass Drink) - Pramono, Andri Pramesyanti; Nugraha, Yudhi; Yulianti, Retno (Journal of Innovation and Community Engagement, 2022)
Coronavirus disease originating from Wuhan, China, has spread throughout the world, including in Indonesia. Covid-19 patients were first detected in Depok, Cinere, West Java, and increased on June 20, 2020. There have been 45,029 positive cases of Covid-19 on June 2021. Gandul Cinere village is located bordered by South Jakarta. Jakarta has a relatively high number of Covid-19 positive patients. Many people lost their jobs during the pandemic, including in the Jakarta and surrounding areas. Anis Baswedan, the governor, expects the unemployment rate due to the Covid-19 Pandemic in the DKI Jakarta area will reach 10 percent in 2021. This shows that economic problems cannot be ruled out easily. Therefore, efforts are needed to improve the economy of UMKM (Usaha Mikro Kecil dan Menengah) to further strengthen Indonesia's economy, especially in the DKI Jakarta and surrounding areas. Red Ginger (Zingiber officinale var Rubrum) and lemongrass (Cymbopogon citratus) are easy to find in Indonesia. Palm Sugar Ginger Lemongrass (MI JAREN) instant drink is an excellent herbal product to be studied and marketed in the Gandul village community. This instant herbal drink-making training was provided online, along with how to package it. The activity results showed that society in Kampung KB Gandul has good knowledge, only still requires guidance for the marketing, especially online. It is hoped that this community service activity can improve the economy in Kampung KB Gandul while also keeping the people of Kampung KB Gandul to avoid COVID-19 infection.